A stepwise strategy integrating metabolomics and pseudotargeted spectrum–effect relationship to elucidate the potential hepatotoxic components in Polygonum multiflorum - Song, Yunfei; Yang, Jianbo; Hu, Xiaowen; Gao, Huiyu; Wang, Pengfei; Wang, Xueting; Liu, Yue; Cheng, Xianlong; Wei, Feng; Ma, Shuangcheng (Frontiers in Pharmacology, 2022)
Polygonum multiflorum Thunb., a typical Chinese herbal medicine with different treatments in raw and prepared forms, has been used worldwide for thousands of years. However, hepatotoxicity caused by Polygonum multiflorum (PM) has raised considerable concern in recent decades. The exploration of toxic components in PM has been a great challenge for a long time. In this study, we developed a stepwise strategy integrating metabolomics and pseudotargeted spectrum-efficiency relationship to illuminate the potential hepatotoxic components in PM. First, 112 components were tentatively identified by Ultraperformance liquid chromatography-quadrupole-time-of-flight-mass spectrometry (UPLC-Q-TOF-MS). Second, based on the theory of toxicity attenuation after processing, we combined the UPLC-Q-TOF-MS method and plant metabolomics to screen out the reduced differential components in PM between raw and prepared PM. Third, the proposed pseudotargeted mass spectrometry of 16 differential components was established and applied to 50 batches of PM for quantitative analysis. Fourth, the hepatocytotoxicity of 50 batches of PM was investigated on two hepatocytes, LO2 and Hep-G2. Finally, three mathematical models, gray relational analysis (GRA), orthogonal partial least squares analysis (OPLS), and back propagation artificial neural network (BP-ANN), were established to further identify the key variables affecting hepatotoxicity in PM by combining quantitative spectral information with toxicity to hepatocytes of 50 batches of PM. The results suggested that 16 components may have different degrees of hepatotoxicity, which may lead to hepatotoxicity through synergistic effects. Three components (emodin dianthrones, emodin-8-O-β-D-glucopyranoside, PM 14-17) were screened to have significant hepatotoxicity and could be used as toxicity markers in PM as well as for further studies on the mechanism of toxicity. Above all, the study established an effective strategy to explore the hepatotoxic material basis in PM but also provides reference information for in-depth investigations on the hepatotoxicity of PM.